Pilot Flight Data Processing System for Airline Management - Phichet Moungnoul (My University, 2023)
This paper presents the development of a pilot flight performance analysis system for airline management designed to show the performance of an aircraft. A system that brings flight data from aircraft then decode to find the relevant parameters. After that, the parameters were analyzed the results of the pilot's flight performance. The results to be displayed by showing the measurement tool then take the parameters obtained to display in a flight simulation. In order to display the event that needs to be monitored by the measurement tool. The flight response caused by the aircraft or operators themselves can be find flaws in the pilot's flight performance.
Keywords: Air Traffic Management and Optimization; Aerospace and Aviation Technology; Target Tracking and Data Fusion in Sensor Networks